A theoretical study on the stability and detonation performance of 2, 2, 3, 3‐tetranitroaziridine (TNAD). (7th March 2014) - Zhang, Xueli; Yang, Junqing; Wang, Tianyi; Gong, Xuedong; Wang, Guixiang
<x xml:space="preserve">Abstract</x> In recent years, there has been a considerable interest in developing high oxygen compounds as oxidizers for, for example, composite explosives. 2, 2, 3, 3‐Tetranitroaziridine (TNAD) is a new designed compound with high oxygen balance (25.11%) and is environmentally friendly. A synthesis route of TNAD was suggested in this study, and the thermodynamic possibilities of reactions were evaluated by the changes in the free energy obtained with the density functional theory (DFT). The strong strain energy (Es = 292.28 kJ/mol) of TNAD leads the C–C bond in the ring more fragile than the C–NO2 bond, and the activation energy (Ea) of pyrolysis of the C–C bond (119.14 kJ/mol at the B3LYP/6‐31G* level of DFT) is higher than that of 2, 4, 6‐trinitrotoluene (TNT) (113.00 kJ/mol). The topological analysis with the contour maps of electron density was used to show the changes of the electron density at the critical points (BCP) in the process of homolysis of the C–C bond. In addition, the energy gap between the frontier orbitals of TNAD (ΔEg = 5.22 eV) is slightly higher than that of 1, 3, 3‐trinitroazetidine (TNAZ, 5.06 eV). And the HOMO → LUMO transition plays important roles in the UV spectrum. The noncovalent interactions in the TNAD/RDX composite were estimated to be stronger than that in TNAZ/RDX, that is, the former may have better compatibility than the latter. TNAD/RDX with the weight ratio of wTNAD/wRDX = 0.46/0.54 has the wonderful performance (D = 9.14 km/s, P = 37.30 GPa, and Is = 285.47 s) which is better than that (D = 8.85 km/s, P = 35.09 GPa, and Is = 272.33 s) of TNAZ/RDX with the same weight ratio. Copyright © 2014 John Wiley & Sons, Ltd.